Pelatihan Pembuatan Sistem Informasi Profil BUMDes di Desa Karang Baru Sebagai Upaya Pengabdian Masyarakat - Jumawal; Mahpuz; Zulkipli; Muh. Farid Wajdi (Jurnal Teknologi Informasi untuk Masyarakat, 2026)
The development of information technology requires Village-Owned Enterprises (BUMDes) to be able to present information quickly, accurately, and transparently to the public to support professional village business management. BUMDes in Karang Baru Village still faces limitations in providing digital information, particularly regarding BUMDes profiles, business units, superior products, and business management activities. This community service activity aims to provide training and assistance in creating a website-based BUMDes profile information system as a medium for information and promotion of village businesses. The implementation method includes observation and analysis of BUMDes needs, system design, development of a BUMDes profile website, training system managers, and evaluation of activity results. This activity was carried out for three months as part of a community service program by students from Hamzanwadi University, involving BUMDes administrators and village officials. The results of the activity show that BUMDes Karang Baru Village has a profile website that contains institutional information, business units, products, activity news, and a documentation gallery. In addition, BUMDes administrators experienced an increase in understanding and skills in managing information systems independently. The conclusion of this activity is that training in creating a website-based BUMDes profile information system can increase information transparency, support village business promotion, and strengthen BUMDes governance in a sustainable manner.